Malta : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that Malta's economic growth languished in 2004 for a fourth consecutive year. Slow growth reflected the weakness of, and increasing competition in, Malta's export markets, as well as domestic factors. The slowdown had begun with shocks to the key sectors, and was reinforced by slow growth in Malta's trading partners and by recent oil price rises. Although growth was weak, the fiscal balance was improved substantially in 2004, and parastatal reform gathered steam.